In vivo Solubilization of Insoluble Chromium Compounds: Hydrolysis of 51Cr-Chromic-32P-Phosphate - Anghileri, Leopoldo J. (Nuklearmedizin - NuclearMedicine, 1968)
The study of distribution and excretion of intravenously injected 51Cr-chromic 32P-phosphate indicates that the organism is capable of complexing a fraction of the radioactivity. This process is similar to solubilization of chromic phosphate by ethylenediaminetetraaceticacid (EDTA). The breakdown of the chromic phosphate molecule appears to occur in the bone marrow. The phosphate ion is incorporated into the mineral tissue of the bone or excreted in the urine. Chromium is bound to protein-like fractions or forms an insoluble hydrate and is excreted almost entirely in the feces.